The role of nanomaterials in enhancing natural product translational potential and modulating endoplasmic reticulum stress in the treatment of ovarian cancer - Singla, Rajeev K.; Sharma, Pooja; Kumar, Dinesh; Gautam, Rupesh K.; Goyal, Rajat; Tsagkaris, Christos; Dubey, Ankit Kumar; Bansal, Himangini; Sharma, Rohit; Shen, Bairong (Frontiers in Pharmacology, 2022)
Ovarian cancer, and particularly its most frequent type, epithelial ovarian carcinoma, constitute one of the most dangerous malignant tumors among females. A wealth of evidence has described the potential of phytochemicals against ovarian cancer. The effect of natural compounds on endoplasmatic reticulum (ER) stress is of great relevance in this regard. In ovarian cancer, the accumulation of misfolded proteins in the ER lumen results in decompensated ER stress. This leads to deregulation in the physiological processes for the posttranslational modification of proteins, jeopardizes cellular homeostasis, and increases apoptotic signaling. Several metabolites and metabolite extracts of phytochemical origin have been studied in the context of ER stress in ovarian cancer. Resveratrol, quercetin, curcumin, fucosterol, cleistopholine, fucoidan, and epicatechin gallate among others have been shown inhibitory potential against ER stress. The chemical structure of each compound plays an important role concerning its pharmacodynamics, pharmacokinetics, and overall effectiveness. Studying and cross - comparing the chemical features that render different phytochemicals effective in eliciting particular anti-ER stress actions can help improve drug design or develop multipotent combination regimens. A number of studies have also investigated the properties of formulations such as nanoparticles, niosomes, liposomes, and intravenous hydrogel based on curcumin and quercetin along with some other phytomolecules in ovarian cancer. Overall, the potential of phytochemicals in targeting genetic mechanisms of ovarian cancer warrants further translational and clinical investigation.